Funcionalidade e hospitalização em idosos internados no Hospital Estadual Bauru - Thomaz, Fernanda Cavalheiro [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Objetivo: Verificar a trajetória da funcionalidade em idosos hospitalizados por condições clínicas e as condições associadas. Método: Estudo observacional descritivo, prospectivo, de coorte, realizado entre 2019 e 2020. Foram avaliados pacientes internados por condições clínicas no Hospital Estadual Bauru. Os idosos foram avaliados quanto às condições sóciodemográficas, causas de internações, funcionalidade com avaliação das atividades básicas de vida diária (ABVD) pela Índice de Katz e presença de Fragilidade (escala FRAIL). Foi realizada descrição da trajetória da funcionalidade em quatro momentos: 15 dias antes da internação (M0), na internação (M1), na alta hospitalar (M2) e 30 dias após a alta (M3). Resultados: Foram avaliados 129 idosos com média de idade de 72,26 (+ 8,14) anos, 50,4% do sexo feminino. Destes 83,8% apresentavam independência funcional em M0; 66,7% no M1; 52% no M2 e 62,8% no M3. De acordo com as trajetórias da funcionalidade verificou-se que 43,4% dos idosos perderam função entre M0 e M3. Houve associação entre piora da funcionalidade entre M0 e M3 e fragilidade (RR 1,45; IC 95% 1,13 – 2,26; p=0,032) e demência (RR 2,26; IC 95% 1,05 – 6,01; p=0,050). Conclusão: Idosos apresentam pior funcionalidade na alta hospitalar quando comparada como momento antes da internação. Cerca de 43,4% dos idosos apresentaram pior função 30 dias após a alta em relação a 15 dias antes da internação. Os idosos com fragilidade e demência apresentam maior risco para resultados funcionais piores após 30 dias da alta.

Objective: To verify the trajectory of functionality in older people hospitalized for clinical conditions and associated conditions. Method: a observational, descriptive, prospective cohort study was conducted between 2019 and 2020. Older people were evaluated regarding sociodemographic conditions, causes of hospitalization, functionality with an assessment of basic activities of daily living (BADL) using the Katz Index and the presence of frailty (FRAIL scale). Older people patients admitted to the Hospital Estadual Bauru, Brazil, were evaluated regarding sociodemographic conditions, causes of hospitalization the functional assessment of basic activities of daily living (BADL) using the Katz Index, and presence of the Frailty (FRAIL Scale). A description of the trajectory of functional capacity was carried out at four times: 15 days before admission (T0), at admission (T1), at hospital discharge (T2), and 30 days after discharge (T3). Results: 129 older people with a mean age of 72,26 (+ 8,14) years, 50.4% of whom were female, were evaluated. Of these, 83.8% presented functional independence at T0, 66.7% at T1, 52% at T2 and 62.8% at T3. According to their functional trajectories, 43.4% of the patients lost functional capacity between T0 and T3. There was an association between worsening of functional capacity between T0 and T3 and the frailty (RR 1.45; IC 95% 1.13 – 2.26; p=0.032) and dementia (RR 2.26; IC 95% 1.05 – 6.01; p=0.050). Conclusion: older patients have worse functional capacity at hospital discharge than before hospitalization. About 43,4% of the older had worse functional capacity 30 days after discharge than 15 days before admission. The older with frailty and dementia have a greater risk for worse functional capacity results 30 days after discharge.
Functionality and hospitalization in elderly hospitalized at the Bauru State Hospital
Keywords: Idosos - Assistência hospitalar; Incapacidade - Avaliação; Idoso fragilizado; Funcionalidade; Hospitalização; Fragilidade; Frail older people; Functionality; Hospitalization; Frailty